Issues in aligning assessments to the Common European Framework of Reference - lvalue lvalue (Universitat Jaume I. Department of English Studies, 2019)
Author/s Spiros Papageorgiou Educational Testing Service, MI, USA   ABSTRACT One of the main aims of the Common European Framework of Reference is to help providers and users of assessments "describe the levels of proficiency required by existing standards, tests and examinations in order to facilitate comparisons between different systems of qualifications" (Council of Europe 2001: 21). Providers of language assessments both inside and outside Europe follow various methodologies to align their assessments with the CEFR levels, as several case studies show (Figueras and Noijons 2009; Martyniuk 2010). This paper discusses the use of the CEFR in the field of language assessment, focusing in particular on issues related to alignment. The paper presents the types of validity evidence that should be accumulated to support an alignment claim and concludes with directions for future research in order to further enhance our understanding of using the CEFR for the design of assessments and the interpretation of assessment results.